(untitled) (Zaporizhzhia Historical Review, 2021)
The author examines the problem of political resolutions’ adopting manner and exertion of power in Soviet society in 1920-1930s. He analyzes different ways of studying this issue: totalitarian, revisionist, Stalinism concept and so on. The author draws conclusion that dictatorship in USSR wasn’t monolithic in spite of highly centralized power character.